Controlled Growth Factor Release in 3D‐Printed Hydrogels. Issue 15 (7th November 2019) - Wang, Pengrui; Berry, David; Moran, Amy; He, Frank; Tam, Trevor; Chen, Luwen; Chen, Shaochen
Abstract: Growth factors (GFs) are critical components in governing cell fate during tissue regeneration. Their controlled delivery is challenging due to rapid turnover rates in vivo. Functionalized hydrogels, such as heparin‐based hydrogels, have demonstrated great potential in regulating GF release. While the retention effects of various concentrations and molecular weights of heparin have been investigated, the role of geometry is unknown. In this work, 3D printing is used to fabricate GF‐embedded heparin‐based hydrogels with arbitrarily complex geometry (i.e., teabag, flower shapes). Simplified cylindrical core–shell structures with varied shell thickness are printed, and the rates of GF release are measured over the course of 28 days. Increasing the shell layers' thickness decreases the rate of GF release. Additionally, a mathematical model is developed, which is found capable of accurately predicting GF release kinetics in hydrogels with shell layers greater than 0.5 mm thick ( R 2 > 0.96). Finally, the sequential release is demonstrated by printing two GFs in alternating radial layers. By switching the spatial order, the delivery sequence of the GFs can be modulated. This study demonstrates how 3D printing can be utilized to fabricate user‐defined structures with unique geometry in order to control the rate of GF release in hydrogels. Abstract : A digital light processing‐based 3D printing system is used to fabricate heparin‐based hydrogels with growth factor in designer structures. Growth factor release kinetics are studied using core–shell structures. To investigate the role of geometry in release kinetics, the thickness of the shell is altered. The growth factor release profiles are measured, and a mathematical model is developed.